Kilka uwag na temat zasady swobodnej oceny dowodów w rzymskim procesie karnym w kontekście „zasady pluralizmu dowodowego” - Nowicka, Dobromiła (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The aim of the article is to examine legal sources in order to draw conclusions on the validity of the principle of free evaluation of evidence in Roman criminal trials from the republican era to the Justinian’s time. The most disputable issue in the matter seems to be the form of evidence appraisal in cognitio extra ordinem, which came to be an ordinary procedure in 3rd century A.D., especially in the light of famous rescript of Constantine seen as a basis for testis unus testis nullus principle, and, as such, as a predecessor of the legal (negative) theory of evidence. However, the constitution in question should not be considered as a breakthrough or a turning point in the matter of evidentiary procedure in Roman criminal trials as it appears rather to be a continuation of earlier regulations concerning procedure in civil cases. Moreover, it seems to be but one of a few manifestations of the principle of evidentiary pluralism which can be understood as basic for Roman criminal proceedings as such.
Keywords: testis unus testis nullus; evidence in Roman criminal trials; the principle of free evaluation of evidence; Constantine on proofs; criminal procedure of ancient Rome